Developing Soft Skills in Future Specialists in Physical Culture and Sports as a Prerequisite for Quality Professional Training - Plachynda, Tetiana (Educological discourse, 2025)
The article highlights the necessity of developing soft skills in future specialists in physical culture and sports, taking into account the specifics of their professional activities. Key aspects of their work include effective interaction with people, managing group dynamics, motivating students and athletes, and making decisions in complex situations. In this context, improving the educational process to foster soft skills is a crucial task in the professional training of specialists in this field. The conducted analysis and systematization of scientific sources confirm that the issue of soft skills development is relevant and requires further research. It is noted that in Ukrainian scientific literature, the English term “Soft Skills” is translated as soft skills and flexible skills, which are often used as synonyms. Additionally, researchers explore the concept of “Meta-skills”, which emphasizes higher-order skills that facilitate the development and management of other competencies. Given the specifics of the professional activities of specialists in physical culture and sports, it is proposed to integrate interactive teaching methods into the educational process of higher education institutions. These methods include training sessions, workshops, business and role-playing games, the case study method, simulation of real professional situations, and analysis of specific cases. Such approaches contribute to the development of communication, leadership, and teamwork skills, which are integral components of “Soft Skills”. The article explores the role and implementation forms of these proposed teaching methods in the educational training of future specialists. The study concludes that the professional training of future specialists in physical culture and sports should be based not only on acquiring professional knowledge but also on developing “Soft Skills”, which determine a modern specialist’s competitiveness. For professionals in physical culture and sports, it is particularly important to develop competencies that foster not only professional growth but also successful self-realization. These specialists must be prepared to work in a dynamic environment, engage in effective communication with stakeholders in their professional activities, and make well-considered decisions in complex professional situations.